GPCR6A Is a Molecular Target for the Natural Products Gallate and EGCG in Green Tea. Issue 8 (14th April 2018) - Pi, Min; Kapoor, Karan; Ye, Ruisong; Smith, Jeremy C.; Baudry, Jerome; Quarles, Leigh D.
Abstract : Scope: The molecular mechanisms whereby gallates in green tea exert metabolic effects are poorly understood. Methods and results: We found that GPRC6A, a multi‐ligand‐sensing G‐protein‐coupled receptor that regulates energy metabolism, sex hormone production, and prostate cancer progression, is a target for gallates. Sodium gallate (SG), gallic acid (GA) > ethyl gallate (EG) > octyl gallate (OG) dose dependently activated ERK in HEK‐293 cells transfected with GPRC6A but not in non‐transfected controls. SG also stimulated insulin secretion in β‐cells isolated from wild‐type mice similar to the endogenous GPRC6A ligands, osteocalcin (Ocn) and testosterone (T). Side‐chain additions to create OG resulted in loss of GPRC6A agonist activity. Another component of green tea, epigallocatechin 3‐gallate (EGCG), dose‐dependently inhibited Ocn activation of GPRC6A in HEK‐293 cells transfected with GPRC6A and blocked the effect of Ocn in stimulating glucose production in CH10T1/2 cells. Using structural models of the venus fly trap (VFT) and 7‐transmembrane (7‐TM) domains of GPRC6A, calculations suggest thatl ‐amino acids and GA bind to the VFT, whereas EGCG is calculated to bind to sites in both the VFT and 7‐TM. Conclusion: GA and EGCG have offsetting agonist and antagonist effects on GPRC6A that may account for the variable metabolic effect of green tea consumption. Abstract : GPRC6A, a family C, nutrient‐sensing G‐protein‐coupled receptor, consists of a venus fly trap motif (VFTM) fused with a 7‐transmembrane (7‐TM) domain. GPRC6A is a molecular target for components of green tea, gallic acid, and EGCG, which respectively activates, and EGCG inhibits GPRC6A signaling. The constructed computational models show a potential relationship between the opening of the VFT hinge and antagonist/agonist behavior.